The Fungus Phlebiopsis flavidoalba’s Pathogenicity and Virulence Toward the Fluted Scale (Praelongorthezia acapulcoa) Pest of Rice and Sugarcane Crops - Silvia Hernández-Hernández; Facundo Muñiz-Paredes; Guadalupe Peña-Chora; Víctor Manuel Hernández-Velázquez (Microbiology Research)
Sugarcane is one of the main crops in Morelos State, Mexico. The presence of the insect pest Praelongorthezia acapulcoa (Morrison), commonly known as the fluted scale insect, was observed in sugarcane and rice crops, causing losses of up to 30% of production in both crops. In this work, a fungus isolated from the mycosic cadavers of P. acapulcoa was identified as the basidiomycete Phlebiopsis flavidoalba (Cooke) Hjortstam via morphological and molecular identification using the ITS, tef 1, and 28S regions. Its pathogenicity toward P. acapulcoa was verified in laboratory tests, causing a mortality rate higher than 60%. Its virulence toward P. acapulcoa, estimated as the mean lethal concentration (LC50), was 9.7 × 106 conidia mL−1. This work constitutes the first report about a basidiomycete with direct entomopathogenic activity and biological control of the fluted scale insect, P. acapulcoa.